2015
DOI: 10.1002/ange.201508473
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Two‐Dimensional Covalent Organic Monolayer through Dynamic Imine Chemistry at the Air/Water Interface

Abstract: A two‐dimensional covalent organic monolayer was synthesized from simple aromatic triamine and dialdehyde building blocks by dynamic imine chemistry at the air/water interface (Langmuir–Blodgett method). The obtained monolayer was characterized by optical microscopy, scanning electron microscopy, and atomic force microscopy, which unambiguously confirmed the formation of a large (millimeter range), unimolecularly thin aromatic polyimine sheet. The imine‐linked chemical structure of the obtained monolayer was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(41 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…[12] The solid-state ordering of shape-persistent macrocycles mimics that of 2D covalent organic frameworks (COFs), whicha re extended, periodics tructures with permanent porositya nd high internal surface areas. These findings provide insight into the crystallization of imine-linked 2D COFs and portendf uture efforts to obtain 2D polymers by cross-linking assembled macrocycles in the solid-state, [23] at the air-water interface, [24] or on surfaces. For example, both boronate ester-linked macrocycles [16] and 2D COFs assemble into layered, hexagonally packed structures through similar nucleation-elongation growth mechanisms.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…[12] The solid-state ordering of shape-persistent macrocycles mimics that of 2D covalent organic frameworks (COFs), whicha re extended, periodics tructures with permanent porositya nd high internal surface areas. These findings provide insight into the crystallization of imine-linked 2D COFs and portendf uture efforts to obtain 2D polymers by cross-linking assembled macrocycles in the solid-state, [23] at the air-water interface, [24] or on surfaces. For example, both boronate ester-linked macrocycles [16] and 2D COFs assemble into layered, hexagonally packed structures through similar nucleation-elongation growth mechanisms.…”
mentioning
confidence: 79%
“…[21] Am echanistics tudy of the 2D COF derived from TAPB and PDA demonstrated that the monomersr apidly condense into an amorphous network that later crystallizes into aT APB-PDA COF. These findings provide insight into the crystallization of imine-linked 2D COFs and portendf uture efforts to obtain 2D polymers by cross-linking assembled macrocycles in the solid-state, [23] at the air-water interface, [24] or on surfaces. Truncated analogueso fT APB react with PDA similarly to first form linear polymers and oligomers (Scheme 1).…”
mentioning
confidence: 79%
“…Various strategies yielding extended sheets of mono-molecular thickness, often described as 2D covalent polymers with a high degree of crosslinking, have been reported in the last few years. [10][11][12] Synthesis at heterogeneous interfaces, vacuum/solid, [13][14][15][16][17][18] air/liquid [19][20][21] , liquid/liquid, 22,23 and in solid phases, [24][25][26] have been demonstrated indeed. All these methods need to be followed by a transfer or exfoliation process, yielding individual layers onto a support of relevance for future applications.…”
mentioning
confidence: 92%
“…[2][3][4][5][6] Both DCC and supramolecular chemistry are adaptable and modular because they allow for the selection and exchange of molecular components. [11] In particular,D CC includes the chemistry of disulfides, [12,13] acetals, [14,15] esters, [16,17] oxime, [18] boroxine, [19,20] alkynes, [21] and imines [22][23][24][25][26][27][28][29] to allow the generation of new covalents tructures. The equilibration processes are much faster in supramolecular systemsw hen compared to DCC systems, because in the latter the covalentb onds need to be broken and reformed.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Whereas classical covalent chemistry operates under kinetic control,t he DCC approacht akes advantage of the reversible natureo fb ond formation to generate new covalent structures under thermodynamic control. [11] In particular,D CC includes the chemistry of disulfides, [12,13] acetals, [14,15] esters, [16,17] oxime, [18] boroxine, [19,20] alkynes, [21] and imines [22][23][24][25][26][27][28][29] to allow the generation of new covalents tructures. Chemicalg roups that include aC =No rc arbonyl units, such as imines,e sters, or amides, are of particular interests ince they can undergo disconnection/reconnection cycles (e.g., trans reactions such as esterification, imination, and amidation).…”
Section: Introductionmentioning
confidence: 99%